ISOLASI, IDENTIFIKASI DAN EVALUASI ANTAGONISME TERHADAP Fusarium oxysporum f.sp. cubense (Foc) SECARA IN VITRO DARI JAMUR ENDOFIT TANAMAN PISANG [Isolation, Identification and Evaluation of Antagonism to Fusarium oxysporum f.sp. cubense (Foc) Under in Vitro Conditions from Endophytic Fungi of Musa sp.] - Suciatmih, Suciatmih; Hidayat, I; Sulistiyani, TR (BERITA BIOLOGI, 2014)
Isolation of endophytic fungi was done to find alternative microorganisms as antifungal agent against Fusarium oxysporum f.sp. cubense (Foc), causing panama disease (fusarium wilt) on Musa spp. The research objectives were 1) to isolate and identify endophytic fungi colonize cavendish (AAA) and rejang (AA) bananas growing on PT Natural Tropical Fruit (NTF) Plantation in East Lampung; and 2) to evaluate for their antagonistic activity against Foc under in vitro conditions. The results indicated 46 isolates of endophytic fungi that were isolated from leaves, saplings and petioles of cavendish banana; and leaves and petioles of rejang banana. The isolated endophytic fungi belonging to the group of Colletotrichum, Fusarium, Guignardia, Penicillium, Talaromyces and non sporulating endophytic fungi that were classified as unidentified isolate. Fourteen isolates (30.43 %) of those 46 fungi isolates tested, showed varying degree of antagonism to Foc. The best three isolates that have strong antagonistic activities were Talaromyces sp. 27-4 (M), unidentified 23-3/11 (B) and unidentified 26-5/K (L). Fusarium oxysporum 22-3/F (I), Penicillium sp. 20-2/H (J), Talaromyces sp. 27-4 (M) and unidentified 21-1/6 (A) inhibited the growth of Foc by producing both volatile and unvolatile metabolites. The strongest inhibition (53.17 %) by volatile inhibitory subtance was produced by F. oxysporum 22-3/F (I), while the strongest inhibition (65.98 %)by unvolatile inhibitory subtance was produced by Penicillium sp. 20-2/H (J).